RESPOSTAS MORFOGENÉTICAS DE JENIPAPEIRO EM DIFERENTES CONDIÇÕES DE CULTURA IN VITRO - CAMILA SANTOS ALMEIDA; ANA VERUSKA CRUZ DA SILVA; APARECIDA GOMES DE ARAÚJO; ANA DA SILVA LÉDO (Revista Caatinga, 2015)
The goal of this paper was to study the morphogenetic responses of jenipapo explants in differ-ent culture conditions in vitro to support multiplication and in vitro production of secondary metabolites proto-cols. After 90 days of cultivation, the jenipapo seedlings were segmented (nodal and leaf segments) and trans-ferred to MS medium supplemented with 30 g L-1 sucrose and different concentrations of 2.4 2.4-Dichlorophenoxyacetic acid -2.4-D (0; 4 and 8 mg L-1) combined with four concentrations of benzilamino-purine- BAP (0; 1; 2 and 3 mg L-1). After 120 days the percentage of explants with morphogenetic response, as is the formation of calluses and/or organogenesis was evaluated. The 2.4-D at concentrations of 4 and 8 mg L-1 induces an increase in morphogenetic response, especially in callus formation, of leaf and nodal segments. The BAP 1.77 mg L-1 induces increased callus formation in leaf segments and induces their higher shoot regenera-tion in leaf and nodal segments. The concentrations of 2.4- D and BAP studied do not induce the formation of somatic embryogenesis in leaf and nodal segments of jenipapo SIR access.